Knitting - Black, Sandy (New York, NY : Abrams, 2011)
History, tradition, and mythology: from the third to the late nineteenth century ##Livelihood and industry: hand- and machine-knitting from the seventeenth to the twenty-first centuries ##Knitting in the home: from the eighteenth century to the present day ##Classics to couture: fashion knitwear from 1900 to now.
boek